2021
DOI: 10.1111/ced.14777
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous anaplastic large‐cell lymphoma: a review of the SEER database from 2005 to 2016

Abstract: Introduction. Primary cutaneous anaplastic large-cell lymphoma (PC-ALCL) is a rare T-cell lymphoma. A prior analysis of the Surveillance, Epidemiology, and End Results (SEER) database reported only 157 cases of localized primary cutaneous CD30+ T-cell lymphoproliferative disorders (PC-ALCL and lymphomatoid papulosis) from 1973 to 2004. Our analysis of the SEER database since 2004 is the largest to date and our results improve our understanding of this disease and their potential prognostic factors. Methods. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…However, factors such as presence of extracutaneous disease, age above 60 years, or extensive limb involvement are considered to be bad prognostic factors. 14 Visceral metastases may occur within 2 months of initial diagnosis to 10 years. 5,15 Previous reported cases with hepatic involvement in C-ALCL have been complied in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, factors such as presence of extracutaneous disease, age above 60 years, or extensive limb involvement are considered to be bad prognostic factors. 14 Visceral metastases may occur within 2 months of initial diagnosis to 10 years. 5,15 Previous reported cases with hepatic involvement in C-ALCL have been complied in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, race, insurance status, and marital status were among the demographic characteristics studied. Age was divided into ≥60 and <60 ( Han et al, 2021 ; Sarfraz et al, 2021 ; Tadros et al, 2021 ; Zhou et al, 2021 ), sex was divided into male and female; race was divided into black, white, and other; single, unmarried or domestic partner, widowed, separated, and divorced were classified as the unmarried group, while the insured/no specifics, insured, and any Medicaid were classified as the insured group. Tumor features included tumor grade (I, II, III, and IV), T stage (T1, T2, T3, and T4), N stage (N0, N1, N2, and N3); the histological type was divided into SCC and other.…”
Section: Methodsmentioning
confidence: 99%
“…61 Similar to MF/SS, some reports found that older age was also associated with unfavorable clinical course. 60,63 Recently, the rearrangement of DUPS22/IRF4 locus on 6p25.3 has been identified in 20-57% cases with PCALCL, [64][65][66] whereas its association with prognosis has not been elucidated yet.…”
Section: Primary Cutaneous Anaplastic Large Cell Lymphomamentioning
confidence: 99%